Night of the zoopocalypse [videorecording (DVD)] (Viva Pictures Distribution, LLC, 2025)
When a meteor crashes into Colepepper Zoo, it unleashes a virus that transforms the zoo animals into zombies. Gracie, a young quirky wolf, teams up with a gruff mountain lion named Dan. Together they lead a team of survivors - including Xavier, the movie-obsessed lemur, Frida the fiery capybara, and Poot the baby pygmy hippo - on a perilous mission to escape the virus and rescue their zoo all on one spooky Night Of The Zoopocalypse!